Effect of rabbit urine foliar spray on the yield and post-harvest quality of tomato (Solanum lycopersicum L.) - Mutua, E. K.; Mwangi, M.; Gaoqiong, L. (International Journal of Horticultural Science, 2024)
Of all vegetable crops, tomato occupies the second-largest cultivated land after potato. However, its production is often lamed by insufficient nutrient supply and invasion by insect pests. Unlike inorganic fertilizers and synthetic pesticides commonly used, rabbit urine supplies nutrients to the crops, controls insect pests and has low mammalian toxicity. However, the most suitable rabbit urine foliar spray concentration for tomato production is currently unknown. The experiment was conducted in a randomized complete block design with six treatments and four blocks to evaluate the effect of different concentrations of rabbit urine foliar spray on the yield and post-harvest quality of tomato. The six treatments used include: five concentrations of rabbit urine (100%, 40%, 25%, 18.2% and 0%) and 0.1% Duduthrin 1.75EC. Results indicated that treatment 18.2% rabbit urine registered the highest marketable yield (129.14 t/ha) in trial 1. In trial 2, treatment 25% rabbit urine recorded the highest marketable yield (165.08 t/ha). These two treatments gave the highest marketable yields due to their sufficient nutrient supply, optimal pest control and zero foliage scorching. Unlike fruit firmness and sugar acid ratio, total soluble solids and titratable acidity increased with increase in rabbit urine concentration. Therefore, a rabbit urine foliar spray concentration of 25% optimally improves yield and post-harvest quality of tomato. More research work can be done to determine the effect of spraying intervals of rabbit urine on the yield and post-harvest quality of tomato.